Development and validation of a risk stratification score for new‐onset atrial fibrillation in STEMI patients undergoing primary percutaneous coronary intervention. Issue 4 (17th April 2018) - Mazzone, Annamaria; Scalese, Marco; Paradossi, Umberto; Del Turco, Serena; Botto, Nicoletta; De Caterina, Alberto; Trianni, Giuseppe; Ravani, Marcello; Rizza, Antonio; Molinaro, Sabrina; Palmieri, Cataldo; Berti, Sergio; et al.
Summary: Aim: New‐onset atrial fibrillation (NOAF) is a complication not infrequent in patients with acute ST‐segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI) and has been associated with worse in‐hospital and long‐term prognosis. We aimed to develop and validate a risk score based on common clinical risk factors and routine blood biomarkers to assess the early incidence of NOAF post‐pPCI, before discharge. Methods: The risk score for NOAF occurrence during hospitalisation (about 5 days) was developed in a cohort of 1135 consecutive STEMI patients undergoing pPCI while was externally validated in a temporal cohort of 771 STEMI patients. Biomarkers and clinical variables significantly contributing to predicting NOAF were assessed by multivariate Cox‐regression analysis. Results: Independent predictors of NOAF were age ≥80 years (6.97 [3.40‐14.30], hazard ratio [95% CI], P < .001), leukocyte count > 9.68 × 10 3 /μL (2.65 [1.57‐4.48], P < .001), brain natriuretic peptide (BNP) > 80 ng/L (2.37 [1.13‐4.95], P = .02) and obesity (2.07 [1.09‐3.92], P = .03). By summing the hazard ratios of these predictors we derived the ALBO (acronym derived from: Age, Leucocyte, BNP and Obesity) risk score which yielded high C‐statistics in both the derivation (0.734 [0.675‐0.793], P < .001) and validation cohort (0.76 [0.688‐0.831], P < .001). In both cohorts, using Kaplan–Meier risk analysis, the ALBO score identified a tertile of patients at highest risk (ALBO >4 points), with percentages of NOAF incidence of 30.8% and 27.4% in the derivation and validation cohort, respectively. Conclusion: The ALBO risk score, comprising biomarkers and clinical variables that can be assessed in hospital setting, could help to identify high‐risk patients for NOAF after pPCI so that a prompter action can be taken.